Compositing nuls proteins for theoretical minimum amino acid score in elastin - Gyimah, Vida (2016)
A thesis submitted to the Department of Food Science and Technology in partial fulfilment of the requirements for the award of the degree of Master of Science in Food Science and Technology, 2015